To protect and to serve: enhancing the efficiency of LAPD recruiting - Lim, Nelson (Rand Corporation monograph series, 2009)
The Los Angeles Police Department (LAPD) is in the middle of a five-year hiring plan to increase the number of sworn officers in the department by 1,000 and achieve a force strength of more than 10,000 officers for the first time in its history. Thus far, working together with the City of Los Angeles Personnel Department's Public Safety Bureau (PSB), the LAPD is on track to achieve this ambitious goal. However, the personnel department and the LAPD have been operating close to the margin, often meeting their hiring quota at the very end of the month. In addition, the LAPD is under consent decrees that stipulate greater diversity in hiring its officers. This book assists the LAPD in achieving its recruiting and diversity goals by offering ways to improve productivity and efficiency in the recruiting process. It begins by identifying potential untapped local recruiting markets. It also provides a model of viable candidates that the LAPD and the personnel department can use to target its recruitment and to prioritize applicants while still maintaining its diversity hiring goal. Finally, it recommends ways to improve productivity of the PSB Background Investigation Division